APPLICATION OF PROBLEM-MODULAR TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Mamadzhanov Sultanali Islamalievich; Khojiev Khairulla Gulomkadirovich; Elmurotov Sharofuddin Polvonovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the use of problematic modular technologies in the organization of the educational process in higher education institutions. Also, this article describes the structure and content of problem-module technology.